A switched‐capacitor‐assisted wireless power transfer system with regulating TX power and fast global loop. Issue 12 (28th April 2022) - Huang, Chenyu; Lu, Yan; Zhan, Chenchang; Martins, Rui P.
Abstract: Wireless power transfer systems demand a regulating transmitter (TX) for global loop control and also a regulating receiver (RX) for its local loop. This design broadens the TX output power range, by merging a switched capacitor (SC) circuit with only 3 switches and 1 flying capacitor to boost the output power of the Class‐D power amplifier. In addition, the transmitting power can be regulated by the duty ratio of the SC, improving the end‐to‐end power transfer efficiency under different load conditions. Moreover, the system obtains fast load transient response, with the help of a light‐to‐heavy load transient enhancement scheme in the TX and the hysteretic control in the RX. Designed in a 0.18‐μm BCD process, this work achieves 3.1 W maximum RX output power, 67.6% peak total efficiency, and 50 μs response time during the light‐to‐heavy load transient simulation.